2010
DOI: 10.1177/0883073810370480
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Toxoplasmosis Accompanied by Facial Nerve Palsy in an Immunocompetent 5-Year-Old Child

Abstract: Acquired toxoplasmosis, although relatively common in children, is usually asymptomatic but can also be clinically manifested by a benign and self-limited infectious mononucleosis-like syndrome. Neurological complications are very rare in immunocompetent children. The authors report a 5-year-old boy who presented with cervical lymphadenopathy because of acquired toxoplasmosis accompanied with unilateral facial nerve paralysis. Toxoplasma gondii DNA detection in blood by polymerase chain reaction, as well as el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Other neurological manifestations during AAT have occasionally been described [2][3][4]. Galli-Tsinopoulou et al reported a 5-year-old boy who presented afebrile with cervical lymphadenopathy, facial nerve palsy without meningeal signs and a negative cerebral MRI [2]. In two cases of encephalitis as a part of disseminated disease, the CSF revealed slight lymphocytic pleocytosis and MRI showed no cerebral pathology [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other neurological manifestations during AAT have occasionally been described [2][3][4]. Galli-Tsinopoulou et al reported a 5-year-old boy who presented afebrile with cervical lymphadenopathy, facial nerve palsy without meningeal signs and a negative cerebral MRI [2]. In two cases of encephalitis as a part of disseminated disease, the CSF revealed slight lymphocytic pleocytosis and MRI showed no cerebral pathology [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Other neurological manifestations during AAT have occasionally been described [2][3][4]. Galli-Tsinopoulou et al reported a 5-year-old boy who presented afebrile with cervical lymphadenopathy, facial nerve palsy without meningeal signs and a negative cerebral MRI [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, CNS toxoplasmosis is extremely rare in immunocompetent hosts and its diagnosis is commonly supported by detection of T gondii antibodies. [3][4][5][6][7] We describe an immunocompetent patient presenting life-threatening cerebral toxoplasmosis in whom both CSF analysis and serology were uninformative and the diagnosis was achieved by means of molecular amplification of T gondii DNA on brain tissue samples.…”
mentioning
confidence: 99%